DESIGN DEVELOPMENT LEARNING JOURNAL REFLECTION FOR THE MEDIA ELEMENTARY SCHOOL TEACHER IN CONDUCTING CLASSROOM ACTION RESEARCH - Suhartono Suhartono (Universitas Muhammadiyah Purwokerto, 2014)
This research was conducted to determine: 1) How to develop the design of learning journals as a reflection of effective elementary school teacher used to conduct classroom action research?, 2) How the results of testing the use of learning journals as a reflection of primary school teachers in conducting action research class?, 3) What are the characteristics, advantages and limitations of learning journals as a reflection of primary school teachers in conducting action research class created?. The purpose of this study are: 1) Explore the development of design learning journals as a reflection of effective primary school teacher and find out the results of testing the use of learning journals as a reflection of primary school teachers in conducting action research class. 2) Identify the characteristics, advantages and limitations of learning journals as a reflection of primary school teachers in conducting action research class developed. Place of research in seven SDN Indramayu district. The research method through the following phases. The number of samples was determined by 30 teachers/students who have taken the S1 PGSD and selected subjects in a way proportional purposive sampling areas as research subjects. Based on the results of the research data showed: 1) Pattern learning journal was developed through three steps of research and development (preliminary studies, planning and development), 2) Pattern learning journal which resulted in the design study journal contains material relating to: objective learning journal as part reflection of teachers in performing and understanding the concept of TOD material (reflective technical), linking them in the context of teachers in the classroom teaching experience (reflective contextual), and critically analyze the material and issues that are taught in the subject through the Class Action Research (reflective critical), 3) Application pattern learning journal, which is conducted through 3 rounds of learning cycle, focused on improving the pattern I and II, 4) Can be applied to each subject because in essence, learning journals elementary classroom teachers can do to perform the TOD with the characteristics of different subjects. Reflections on learning with the implementation of learning journals can do in times of learning (reflective in teaching), after learning (reflective on teaching), and for the next teaching (reflection for teaching), through self and shared analysis